Sub-regionalism and international river basins : evaluating the integration of the Mekong and Danube - Soavapa Ngampramaun; Ploberger, Christian (Newcastle upon Tyne : Cambridge Scholars Publishing, 2020)
This book investigates the origins and dynamics of sub-regional phenomena based on international river basins, namely the Mekong and Danube rivers. It emphasizes the integration process of the Greater Mekong Sub-region and the European Strategy for the Danube Region, which are located in two different geopolitical and structural settingsone in Southeast Asia in the regional context of the Association of Southeast Asian Nations (ASEAN), and the other in Central and Eastern Europe within the regional context of the EU. By comparing two unique case studies within different structural settings, additional and valuable insights into the occurrence and formation of sub-regional integration processes are provided, enabling an evaluation of similarities and differences. Understanding sub-regional integration dynamics requires not only looking upward to the regional and even the global level, but indeed looking downwards to the local level. After all, sub-regional integration processes are generally described as bottom-up processes, based on local interests and expectations. Despite the growing number of sub-regional projects, sub-regionalism remains inadequately studied in the field of political science, and, as such, this book offers unique contributions to the understanding of sub-regional integration processes. Consequently, it will be of interest to readers who are interested in regional and sub-regional integration processes, as well as those with a specific interest in both the EU and ASEAN geographic regions.
Includes bibliographical references.
Keywords: Regionalism -- Asia; Regionalism -- European Union countries; Mekong River; Mekong River Valley; Danube River; Danube River Valley